Penerapan Metode Bertahap Untuk Meningkatkan Keterampilan dan Hasil Belajar Passing dalam Permainan Bola Voli - Kusmiran Kusmiran (Peneliti.net, 2022)
The purpose of this study was to obtain empirical data on the application of the step-by-step method to improve skills and learning outcomes of passing in volleyball games. This research is a classroom action research (CAR), which uses direct observational data on the learning process. The results show that through the application of the stepwise method in learning the basic techniques of volleyball passing, it can improve the learning outcomes of students' passing knowledge and skills in grades VII-H of junior high school. State 1 Jekulo. This is indicated by an increase in learning outcomes of knowledge and skills.